Application of the E-Bussines Concept to a Double Bread Company (Case Study of FEBI UINSU Students) - Arbarija Hafiz Lbs; Erlangga Hakim Manurung; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
With the large number of fans of Roti Ganda outside the Pematang Siantar area, therefore an E-business implementation system is needed in the company. The use of e-business technology facilitates company performance and improves company quality. The application of this technology can expand the company's market share, especially the cost for advertising which is cheap compared to advertising on the street and mass media. There needs to be socialization and in-depth learning as well as careful preparation before implementing e-business applications. In the process of designing the application of E-Business at a web- based Double Bakery Shop with a CRM (Customer Relationship Management) approach, an explanation or theory is needed that can support and support success in making the information system and to explain to users how the functions and benefits of implementing E-Business are needed. on a web-based Double Bakery with a CRM approach.